Canadian Society of Transplantation and Canadian Society of Nephrology Commentary on the 2017 KDIGO Clinical Practice Guideline on the Evaluation and Care of Living Kidney Donors. (June 2020) - Lam, Ngan N.; Dipchand, Christine; Fortin, Marie-Chantal; Foster, Bethany J.; Ghanekar, Anand; Houde, Isabelle; Kiberd, Bryce; Klarenbach, Scott; Knoll, Greg A.; Landsberg, David; Luke, Patrick P.; Mainra, Rahul; et al.
Purpose of review: To review an international guideline on the evaluation and care of living kidney donors and provide a commentary on the applicability of the recommendations to the Canadian donor population. Sources of information: We reviewed the 2017 Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline on the Evaluation and Care of Living Kidney Donors and compared this guideline to the Canadian 2014 Kidney Paired Donation (KPD) Protocol for Participating Donors. Methods: A working group was formed consisting of members from the Canadian Society of Transplantation and the Canadian Society of Nephrology. Members were selected to have representation from across Canada and in various subspecialties related to living kidney donation, including nephrology, surgery, transplantation, pediatrics, and ethics. Key findings: Many of the KDIGO Guideline recommendations align with the KPD Protocol recommendations. Canadian researchers have contributed to much of the evidence on donor evaluation and outcomes used to support the KDIGO Guideline recommendations. Limitations: Certain outcomes and risk assessment tools have yet to be validated in the Canadian donor population. Implications: Living kidney donors should be counseled on the risks of postdonation outcomes given recent evidence, understanding the limitations of the literature with respect to its generalizability to the Canadian donor population.